Effect of metal nanoparticle concentration on localized surface plasmon mediated Förster resonant energy transfer - Bradley, Louise; Gounko, Iouri (My University, 2012)
The influence of gold nanoparticle concentration on signatures of localized surface plasmon mediated Förster resonant energy transfer is investigated in a quantum dot–gold nanoparticle sandwich structure. At lower gold nanoparticle concentrations, localized surface plasmon mediated Förster resonant energy transfer enhancement of the acceptor emission is observed. At higher gold nanoparticle concentrations, the acceptor emission is reduced despite faster localized surface plasmon enhanced Förster resonant energy transfer rates being achieved. This is attributed to competition between localized surface plasmon mediated Förster resonant energy transfer and gold nanoparticle quenching effects.
PUBLISHED
Keywords: Quantum dots; Nanocrystals; Colloidal metal nanoparticles; Localised surface plasmons; Förster resonant energy transfer; Non-radiative energy transfer